⌈ 2 ⌉ × ⌈ 3 ⌉ × ⌈ 4 ⌉ × ⋯ × ⌈ 9 9 ⌉
Find the largest non-negative integer n such that 2 n is a factor of the number above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! +1.
The question asks for generalization. Although I have made some progress to generalize the solution, I couldn't yet figure out how to do this. Any ideas?
Did the same
Suppose that the expression is equal to A. Then, A = 2 3 × 3 5 × 4 7 × 5 9 × 6 1 1 × 7 1 3 × 8 1 5 × 9 1 7 × 1 0 1 8 Asked : The largest non-negative integer n such that 2 n is a factor of A So, n = 3 + 2 × 7 + 1 1 + 3 × 1 5 + 1 8 Then, n = 9 1
Ununderstandable!!!!! Solution!!!?
Log in to reply
W e f i n d h o w m a n y ⌈ N ⌉ g i v e s 2 , 4 , 6 , 8 , b u t l i m i t i s 9 9 . 1 2 + 1 = 2 . . . . . . . . . . . t o . . . . . . . . 2 2 = 4 . . . . . . 4 − 2 + 1 = 3 o f 2 . 3 2 + 1 = 1 0 . . . . . . . . . . . t o . . . . . . . . 4 2 = 1 6 . . . . . 1 6 − 1 0 + 1 = 7 o f 2 2 . 5 2 + 1 = 2 6 . . . . . . . . . . . t o . . . . . . . . 6 2 = 3 6 . . . . . 3 6 − 2 6 + 1 = 1 1 o f 2 ∗ 3 . 7 2 + 1 = 5 0 . . . . . . . . . . . t o . . . . . . . . 8 2 = 6 4 . . . . . 6 4 − 5 0 + 1 = 1 5 o f 2 3 . 9 2 + 1 = 8 2 . . . . . . . . . . . t o . . . . . . . 1 0 2 = 1 0 0 . . . . . 1 0 0 − 1 6 + 1 = 1 9 o f 2 ∗ 5 . S o f r o m 1 t o 1 0 0 , w e h a v e n = 3 + 2 ∗ 7 + 1 1 + 3 ∗ 1 5 + 1 9 = 9 2 . B u t o u r l i m i t i s u p t o 9 9 , w h i l e w e h a v e i n c l u d e d 1 0 0 . S o f r o m s q u a r e r o o t o f 1 t o 9 9 w e h a v e 2 9 2 − 1 . ⟹ n = 9 1 .
I solved it too this way but you need to detail it with all steps.
Is there any way to generalize it not only for 2 but for other prime factors too?
Problem Loading...
Note Loading...
Set Loading...
Let the product be P , then we have:
P = ⌈ 2 ⌉ × ⌈ 3 ⌉ × ⌈ 4 ⌉ × ⌈ 5 ⌉ × ⌈ 6 ⌉ × ⌈ 7 ⌉ × ⌈ 8 ⌉ × ⌈ 9 ⌉ × ⌈ 1 0 ⌉ × . . . × ⌈ 9 9 ⌉ = 2 × 2 × 2 × 3 × 3 × 3 × 3 × 3 × 4 × . . . × 1 0 Note: ⌊ m ⌋ increases by 1 when m − 1 is a perfect square. = 2 4 − 1 3 9 − 4 4 1 6 − 9 . . . k k 2 − ( k − 1 ) 2 . . . 1 0 9 9 − 8 1 = 2 3 3 5 4 7 5 9 6 1 1 7 1 3 8 1 5 9 1 7 1 0 1 8 = 2 3 ( 2 2 ) 7 ( 2 1 1 3 1 1 ) ( 2 3 ) 1 5 ( 2 1 8 5 1 8 ) 3 5 5 9 7 1 3 9 1 7 = 2 3 + 1 4 + 1 1 + 4 5 + 1 8 3 1 6 5 9 7 1 3 9 1 7 = 2 9 1 3 1 6 5 9 7 1 3 9 1 7
⇒ n = 9 1 .